Polarization-independent electro-absorption optical modulator based on trapezoid polymer-graphene waveguide. (May 2022) - Lian, Tianhang; Yang, Kaidi; Sun, Shijie; Zhu, Mu; Yue, Jian; Lin, Baizhu; Sun, Xiaoqiang; Wang, Xibin; Zhang, Daming
Highlights: A polarization-independent electro-absorption modulator based on the trapezoid polymer-graphene waveguide was proposed. The insulting dielectric spacer sandwiched in the two graphene layers can be placed inside the polymer waveguide. The presented modulator has a compact size and a higher extinction ratio. The presented modulator has potential applications in the on-chip optical interconnect system. Abstract: A polarization-independent electro-absorption modulator based on the trapezoid polymer-graphene waveguide (PGW) was proposed. The modulator was constructed on a trapezoid polymer waveguide, and the insulting dielectric spacer sandwiched in the two graphene layers was placed on the surface of the trapezoid polymer waveguide core. The simulation results show that by applying different gate voltages on the graphene layers, effective mode index of the TE and TM modes in the PGW can realize the similar changes in the C-band, which provides the possibility for realizing the polarization-independent modulation. Here, through simulation and optimization, the presented modulator has a compact size and the extinction ratio (ER) of 37 dB can be achieved by reasonably setting working points of "OFF" and "ON" states with 800 μm long active graphene length. The ER variation between the two operating modes is about 0.46 dB. The corresponding power consumption of the modulator is about 23.6 pJ/bit.